HUBUNGAN SIKAP SOSIAL SISWA DENGAN PRESTASI BELAJAR DI SD BINA BUDI MULIA MALANG - Mia Karnila (Sekolah Tinggi Agama Buddha Negeri Raden Wijaya, 2021)
This research aims to determine the level of social attitudes at SD Bina Budi Mulia Malang, to determine the relationship of social attitudes to learning achievement. The research using census research design with quantitative descriptive methods. The data obtained from the questionnaire distribution analyzed using a Likert scale and Pearson correlation coefficient with t-test and document data in form of values. The results of this study indicate that there is a significant relationship between social attitudes and learning achievement. From the results of the study obtained a significant value of responsibility attitude with 85%, honest attitude with 86%, discipline attitude witSh 85%, caring attitude with 64%, polite attitude with 91% and self-confidence with 84% achievement. The correlation coefficient value of the relationship between social attitudes and learning achievement is 0.619 so it can be concluded that there is a significant linear relationship between social attitudes (X) and learning achievement (Y).